Learning and education after sustainability. Issue 1 (2nd January 2017) - Scott,
Abstract : This is a reply to:Gough, Steve. 2017."Education after sustainability." Global Discourse . 7 (1): 131–145. http://dx.doi.org/10.1080/23269995.2017.1300435 .